Asymmetric white matter degeneration in amyotrophic lateral sclerosis: a diffusion kurtosis imaging study of motor and extra-motor pathways - Juan Carlos Quizhpilema; Ane Legarda; José Manuel Hidalgo; Pablo Lecumberri; Ivonne Jerico; Ivonne Jerico; Teresa Cabada; Teresa Cabada (Frontiers in Neuroscience)
BackgroundAmyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease that lacks effective early biomarkers. This study investigated the potential of diffusion kurtosis imaging (DKI) as a non-invasive biomarker for detecting and monitoring ALS progression through a comprehensive analysis of white matter alterations.MethodsWe performed a cross-sectional analysis of magnetic resonance images with advanced diffusion imaging techniques in ALS patients recruited from a neurodegenerative consultation service over a 3-year period and healthy controls. Our methodology employed multi-shell multi-tissue constrained spherical deconvolution (MSMT-CSD) for tract reconstruction and diffusion kurtosis imaging for microstructural analysis. The study focused particularly on the corticospinal tract and associated pathways, utilizing both tract-specific Bundle Analytics (BUAN) and whole-brain Tract-Based Spatial Statistics (TBSS) approaches.ResultsThe study included 33 ALS patients and 37 controls with no significant differences in age or gender. ALS patients predominantly presented with spinal onset and exhibited moderate functional impairment (ALSFRS-R: 39.09 ± 5). Whole-brain TBSS revealed widespread white matter alterations, with increased MD, RD, and AD, and decreased FA notably in the corona radiata, internal capsule, and corticospinal tracts. Detailed fiber tracking of the corticospinal tracts showed significant microstructural changes, with the left CST displaying pronounced increases in MD and AD alongside reduced FA, while the right CST exhibited distinctive regional variations. Additionally, analyses of the frontopontine and parietopontine tracts uncovered further alterations in diffusion metrics. Despite imaging findings, clinical-radiological correlations with functional scores and disease progression were not statistically significant.ConclusionsThis study explores DKI as a potential biomarker for ALS pathology, revealing microstructural changes in both motor and extra-motor pathways. Using whole-brain TBSS analysis and tractography with DIPY, we identified an asymmetric pattern of degeneration and involvement of integrative neural networks, providing new insights into ALS pathophysiology. These findings contribute to our understanding of the complex structural alterations in ALS and suggest that DKI-derived metrics may have utility in characterizing the disease process.